Evaluation of prescription errors and prescribing indicators in the private practices in Bahawalpur, Pakistan. Issue 5 (May 2018) - Atif, Muhammad; Azeem, Muhammad; Sarwar, Muhammad Rehan; Malik, Iram; Ahmad, Wajiha; Hassan, Fariha; Rehman, Ayesha; Rana, Mahjabeen
Abstract : Background: : Appropriate use of medicines is important to provide quality health. The aim of this study was to assess the prescribing practices and prescription errors in the private clinic practices of Bahawalpur, Pakistan. Methods: : A cross‐sectional observational study was performed in March 2015 to assess the prescribing practices and prescription errors in the private clinical practices of Bahawalpur, Pakistan. We used the standard World Health Organization (WHO) methodology to achieve the study objectives. A convenience sampling technique was used to collect the prescriptions from five community pharmacies. Results: : A total of 300 prescriptions were collected. Among the prescribing indicators, the average number of drugs per encounter was 4.5, 23.3% of drugs were prescribed by generic name, 39.6% of encounters resulted in the prescription of antibiotics, in 19% of encounters injections were prescribed and 54.5% of the drugs prescribed were from the Essential Drugs List. A total of 1218 omissions, 510 commissions and 199 drug interaction‐related errors were recorded. Conclusion: : Irrational prescribing of medicines and low compliance with the standards of prescription writing were observed in the private clinical practices of Bahawalpur.